Analysis of the management of environmental proactivity and its structural determinants in the field of hotel - García-Pozo, Alejandro; Sánchez-Ollero, José Luis; Del-Cubo-Arroyo, Elisa (My University, 2014)
Recent literature has shown that a firm's environmental commitment can be a potential source of comparative advantage and may translate into higher revenues that could offset the additional costs involved in implementing environmentally friendly measures. Environmental commitment may be due to pressure from consumers who demand good environmental practices from hotels, which in turn could result in the hotels making business decisions that manifest as environmentally proactive measures by the establishment. Together with these hotel management measures, establishments have other structural factors (such as their location or hotel category) that may influence the implementation of environmentally proactive policies. Using discrete choice binomial logit model, this article analyzes the impact of business policy and structural factors on the probability that a hotel establishment can be considered environmentally proactive.
Keywords: Hostelería - Aspectos ambientales; Hotel; Environment